Climatic influences on intra-annual stem variation of Larix principis-rupprechtii in a semi-arid region - Li, Weixin; Yue, Fengxin; Wang, Chunkai; Liao, Jinglei; Zhang, Xianliang (Frontiers in Forests and Global Change, 2022)
Intra-annual monitoring of stem radial growth dynamics of trees and detecting how tree growth responds to changing climatic conditions is crucial for predicting the future growth dynamics under increasing drought conditions. Here, we monitored the intra-annual stem radial growth dynamics of seven L. principis-rupprechtii using point dendrometers to investigate the influence of climate variables on the intra-annual growth of L. principis-rupprechtii in the growing season. The average stem radial growth of L. principis-rupprechtii started on 29 April and stopped on 17 August based on the sigmoid Gompertz functions. The intra-annual stem radial growth of L. principis-rupprechtii showed a parabolic trend, with its growth decreased when the temperature and sunlight duration hours exceeded certain thresholds. The VPD strongly influenced tree intra-annual growth over other climatic factors in the growing season. Stem radial growth of L. principis-rupprechtii decreased significantly with increasing VPD when VPD ranged from 0.5 kPa to 0.8 kPa. Intra-annual stem radial growth of L. principis-rupprechtii was severely inhibited when VPD was higher than 0.8 kPa. In contrast, tree stem radial growth reached the maximum when VPD was lower than 0.5 kPa. Our study highlighted the important influences of major limiting climatic factors on the stem radial growth of trees in semi-arid regions.